Polymerase chain reaction versus enzyme-linked immunosorbent assay in detection of Chlamydia trachomatis infection among gynaecological patients in southwestern Nigeria. (2018)
Background: Chlamydia trachomatis (C. trachomatis), is the most common bacterial Sexually Transmitted Infection, a major cause of Pelvic Inflammatory Disease and female infertility. Since C. trachomatis infections are frequently asymptomatic with higher prevalence in developing countries, highly sensitive and affordable methods are desirable for routine screening and diagnosis. This study aimed to evaluate the performance of C. trachomatis-specific IgG antibody by ELISA as a screening tool for C. trachomatis infection, by comparing the performance of ELISA with the gold standard Polymerase Chain Reaction( PCR). Method: In this cross sectional study, we enrolled 150 women attending infertility clinic at Ibadan between January and November, 2015. ELISA for detection of IgG antibodies specific to C. trachomatis major outer membrane protein (MOMP) was performed on the blood samples using third generation indirect Enzyme Linked Immunosorbent Assay (ELISA) and endocervical samples were analyzed for presence of C. trachomatis nucleic acid using PCR. Socio demographic bio-data and gynaecological history were obtained with questionnaire; data was analyzed using SPSS version 20.0. Results: Overall, 58 (38.7%) were positive for C. trachomatis specific IgG antibody by ELISA and 11 (7.3%) for C. trachomatis nucleic acid by PCR. Using PCR as the gold standard, ELISA had a sensitivity of 81.8% specificity of 64.8%, positive predictive value of 15.5% negative predictive value of 97.8% and accuracy of 66%. Conclusion: The high sensitivity of the ELISA indicates that over 80% of patients identified as being positive in the screened population are truly infected. Also, the negative predictive value approaches 100% amongst those screened out as being negative. Thus its use as a screening tool for C. trachomatis infection is warranted particularly in developing countries where cheaper and easier to use alternatives to PCR are in dire need.